Biosynthesis of Metallic Nanoparticles from Plants: Industrial Applications - Rodica CHIHAI (PEȚU); Claudia Veronica UNGUREANU; Alina CEOROMILA (ACROSS)
The biosynthesis of metallic nanoparticles from plants is a very wide field, which has attracted increasing interest lately due to their unique properties. Nanoparticle production volumes around the world are increasing due to their widespread application, especially in technology and science. The chemical and physical methods used to make the nanoparticles are often expensive and potentially dangerous to the environment. Biosynthesis is an alternative, inexpensive, efficient and environmentally friendly method of obtaining nanoparticles with the desired properties. This approach is carried out by various macro- and microscopic organisms, such as plants, fungi, bacteria, algae and microalgae. A major factor is the natural plant compounds involved in the bioreducing of metal salts during the synthesis of nanoparticles. Plants contain natural compounds such as alkaloids, flavonoids, saponins, steroids, tannins, and other nutrients. They have been used in the synthesis of various nanoparticles such as silver, gold, copper, cobalt, zinc oxide, palladium, platinum, and others. The main advantages of this approach are the low cost, the short preparation time of the final product and the biological safety.